Implementasi Pembelajaran Inklusif untuk Mengembangkan Keterampilan Sosial Anak Berkebutuhan Khusus (ABK): Sebuah Studi Kasus - Nur Khomsidah; Zainal Arifin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Children with Special Needs (ABK) are often identified differently by society, even though they actually have the same rights as children in general to participate in social life. ABK need guidance to improve their ability to interact with their surrounding environment. The aim of this research is to find out the effective steps that have been taken by inclusive schools in assisting and developing their social skills along with the supporting and inhibiting factors. This research is a qualitative descriptive research using the case study method. Data was collected through observation, documentation and interviews. Then the data was analyzed using Miles and Huberman's interactive approach. As a result, there are many effective steps at this school that can be implemented by other schools in developing the social skills of ABK. And shows the development of ABK's social skills over various times. Slowly positive changes can be observed after one semester and more significant ones are formed when entering the 4th year after implementing these steps. There are also supporting and inhibiting factors which have been prepared to be resolved together with the student's parents.